Visceral adipose tissue according to magnetic resonance imaging as a factor associated with leptin resistance in stable coronary artery disease - N. I. Ryumshina; О. A. Koshelskaya; N. V. Naryzhnaya; O. A. Kharitonova; E. S. Kravchenko; K. V. Zavadovsky (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate quantitative and radiomic characteristics of abdominal visceral adipose tissue (VAT) using magnetic resonance imaging (MRI), their relationship with lipid, carbohydrate metabolism, inflammation in patients with coronary artery disease (CAD), as well as the association of these factors with leptin resistance (LR).Material and methods. The study included 46 patients with stable CAD. MRI was performed to determine the volume (cm3) of abdominal adipose tissue. The serum levels of glucose and insulin, lipid profile, proinflammatory markers and adipokines were determined. For quantitative assessment of LR, the free leptin index (FLI) was calculated (FLI >25 indicates LR).Results. In the group with LR, body mass index and homeostasis model assessment of insulin resistance (HOMA-IR), the levels of insulin, adiponectin, leptin and FLI were significantly higher, while the adiponectin/leptin ratio and the blood level of leptin receptors were lower than in the group of patients without LR. No intergroup differences in abdominal fat volume were found. The group with LR was characterized by a significantly lower value of such radiomic characteristics as Entropy and Variance. The following factors associated with LR were included in the multivariate logistic regression analysis model: age (odds ratio (OR) 1,24, 95% confidence interval (CI): 1,05-1,47), glucose level (OR 2,50, 95% CI: 0,73-8,62), soluble leptin receptor level (OR 0,65, 95% CI: 0,47-0,91), smoking (OR 0,43, 95% CI: 0,065-2,89) and Entropy (OR 2,44, 95% CI: 0,13-46,5). The sensitivity and specificity of the model are 90,6 and 57,1%, respectively.Conclusion. Significant factors associated with LR in patients with stable CAD were identified: Entropy, older age, high glucose levels, smoking, and low levels of soluble leptin receptors.